Inovasi Pemanfaatan Jantung Pisang: Strategi Pemberdayaan Masyarakat Desa Karya Mukti Kecamatan Sinar Peninjauan - Merita Auli; Rizki Ayu Damayanti; Serly Margareta; Fitra Juli Pramana (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
The work program carried out in the implementation of the Real Work Lecture in Karya Mukti Village, Sinar Pereviewuan District focuses on the innovation of using banana hearts as an effort to empower the village community. Banana hearts are often considered waste from the banana tree itself, it turns out that banana hearts have great potential to be processed into products with more economic value. This community service activity aims to further explore the potential of the banana heart, develop processing innovations and see its impact on improving community skills and economy. The method used is a participatory approach through socialization, practice and assistance to the community in processing banana hearts into chips. The results show that the public's enthusiasm for banana heart processing is increasing, and the products produced can be marketed locally. Innovation in the use of banana hearts into processed banana heart chips can be an effective strategy for community empowerment and should be accompanied by continuous training and marketing support.